Lived experience, power that a degree cannot give you: a phenomenological study of one Hispanic woman leader in academia - Perez, Mayra; Kelley, Allyson; Ceballos, Venice; Milligan, Kelley; Cabrera, Alejandra (Frontiers in Education, 2024)
Structural racism, bias, and discrimination within institutions of higher education prevent Hispanic women from becoming university leaders and professors, especially when they do not have a formal degree (Inglebritson, 2019;Marrero-Lopez, 2015). Only 16% of academic senior program leaders are minorities, and very few are Hispanic women (Bridges et al., 2007;Montas-Hunter, 2012). Hispanic individuals occupy just three percent of faculty positions (National Center for Education Statistics, 2021), and Hispanic women in higher education represent just 2 percent of faculty and leadership positions (Bonomi, 2020). Data from the National Center for Education statistics underscores this lack of Latinas in academia, with slow progress; in 1991, Latinas represented <1% of all full-time faculty, and in 2019, this increased to just 2.6% (Abraido-Lanza et al., 2022). The diverse representation of Latinas is due to systemic and longstanding inequities. While educational attainment among Hispanic women has grown substantially over the last several decades, higher education attainment still falls behind that of white women. Across the United States, 51% of White women have a college degree, which is nearly double that of Hispanic women at 27% (ACS, 2018). This further limits the likelihood of a Hispanic woman in positions of leadership within academic institutions despite cultural, social, and contextual knowledge of the community and settings within which many academic institutions work. There are initiatives in place, such as the White House Initiative on Advancing Educational Equity, Excellence, and Economic Opportunity for Hispanics, to improve the pipeline to education and increase degree attainment among Hispanic adults.